Green Synthesis of Silver Nanoparticles from Stem Extracts of Caralluma Fimbriyata and Its Antibacterial Activity - Packialakshmi, N.; Naziya, S. (International Journal of Applied Sciences and Biotechnology, 2014)
The aim of this study was to synthesis of silver nanoparticles in the aqueous stem extracts of Caralluma fimbriyata and investigate its antibacterial activity. Nanoparticles are being used in many commercial applications. It was found that aqueous silver ions can be reduced by aqueous stem extracts of plant parts to generate to extremely stable silver nanoparticles in water. The chemical groups studied using FT-IR analysis. Green synthesized silver nanoparticles showed zone of inhibition against isolated gram positive and gram negative bacteria. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10796 Int J Appl Sci Biotechnol, Vol. 2(3): 305-310